Development Model of the Batik Harmoni SMI Cluster in North Sumatera: Post-COVID-19 Strategies and Solutions - Rizal Agus (Walidem Institute and Publishing, 2026)
Objective: This study aims to develop a cluster development model for Batik Harmoni MSMEs in North Sumatra using the Analytic Network Process (ANP) to identify priority solutions and strategies in the post-COVID-19 era. Theoretical Framework: This study is based on the theory of MSME cluster development, performance-based competitiveness, and crisis resilience theory, considering the interdependence between internal capabilities and external environmental factors. Literature Review: Criteria and Performance of Micro, Small, and Medium Enterprises (MSME), The Relationship between MSME Clusters and Business Performance, The Source of Working Capital, The Relationship between HR and Business Performance, The Connection Between Marketing Mix and Business Performance. Method: A mixed qualitative-quantitative approach was used through focus group discussions, in-depth interviews, and paired comparison questionnaires involving seven expert participants, with data processed using Super Decisions software and analyzed through priority weighting and Kendall's concordance coefficient. Results: The findings indicate that internal solutions are the highest priority, led by performance, followed by human resources, marketing mix, and business size, with total sales and profit margin as key performance indicators, training as the top human resource solution, product as the dominant marketing mix element, and working capital as the main business size factor. Externally, the economic environment during COVID-19, working capital, and government support, particularly technological assistance, were the most influential factors. Implications: The results suggest that post-pandemic MSME cluster development should prioritize strengthening internal performance supported by technology-based policies and institutional support. Novelty: This study offers an integrated ANP-based development model that systematically links the internal and external determinants of the resilience and competitiveness of batik MSME clusters in developing countries.